2000
DOI: 10.1002/1521-3773(20000804)39:15<2632::aid-anie2632>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Acetylenic Coupling: A Powerful Tool in Molecular Construction

Abstract: Acetylenic coupling is currently experiencing some of the most intensive study of its long history. Rigid and sterically undemanding di- and oligoacetylene moieties, which are frequently encountered in natural products, are finding increasing application as key structural elements in synthetic receptors for molecular recognition. Interesting electronic and optical properties of extensively pi-conjugated systems have spurred research into new linear oligoalkynes and acetylenic carbon allotropes. The synthetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
640
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 463 publications
(659 citation statements)
references
References 0 publications
11
640
0
8
Order By: Relevance
“…Quite surprisingly, despite the wide and diverse use of acetylene ''building blocks'' in solution-phase chemistry, 165 there are few published studies, apart from CuAAC reactions, that have reported on the unique properties of the carbon-carbon triple bond in the context of derivatizing solid substrates. We predict alkyne-alkyne coupling will become increasingly popular.…”
Section: Acetylenic Couplingmentioning
confidence: 99%
“…Quite surprisingly, despite the wide and diverse use of acetylene ''building blocks'' in solution-phase chemistry, 165 there are few published studies, apart from CuAAC reactions, that have reported on the unique properties of the carbon-carbon triple bond in the context of derivatizing solid substrates. We predict alkyne-alkyne coupling will become increasingly popular.…”
Section: Acetylenic Couplingmentioning
confidence: 99%
“…[237] First attempts using a classical Sonogashira cross coupling protocol mainly provided diacetylenes as product, probably due to a copper ion catalyzed oxidative acetylene homo-coupling reaction. [245] [246] To avoid this competing homo-coupling protocol was chosen. [147] It has to be mentioned that copper ions were added.…”
Section: General Protocol For the Sonogashira Cross Coupling Reactionmentioning
confidence: 99%
“…[6] We hypothesized that the catalytic copper(I) species is generated upon reduction of copper(II) by either an oxidizable solvent such as methanol [7] or the terminal alkyne substrate by means of the oxidative homocoupling reaction. [8] A subset of the azide substrates rapidly convert to triazole products under the CuA C H T U N G T R E N N U N G (OAc) 2 -mediated conditions. Those azides, which are termed "chelating azides," contain auxiliary ligands capable of assisting the azido group in binding the copper centre.…”
Section: Introductionmentioning
confidence: 99%